Older Age Is the Strongest Predictor of Postoperative Atrial Fibrillation - Amar, D. (Institutional Knowledge at Singapore Management University, 2002)
Background: Identification of patients vulnerable for atrial fibrillation (AF) after major thoracic surgery will allow targeting those most likely to benefit from prophylactic therapy. The goal of the current study was to evaluate the accuracy of easily available clinical characteristics for the prediction of this complication. Methods: Patients undergoing major elective thoracic surgery were chosen from an ongoing prospective database. Results: Postoperative in-hospital AF occurred in 79 (15%) of 527 patients Using cut-point methodology and logistic regression, the authors identified two preoperative risk factors independently associated with AF: age 60 yr or older (P = 0.0007) and heart rate 74 beats/min or greater on preadmission electrocardiogram (P = 0.005). The odds of developing AF increased by a factor of 2.5 (95% confidence interval, 1.7-3.4; P < 0.0001) between incremental age categories ( < 60 yr, 60-69 yr, ? 70 yr) and by a factor of 2.3 (95% confidence interval, 1.4-3.8; P < 0.0007) between heart rate categories (< 74 beats/min, ? 74 beats/min). The combination of age 60 yr or older and preoperative heart rate 74 beats/min or greater predicted AF with a sensitivity of 73% and specificity of 57%. Maximum P-wave duration as measured from standard electrocardiogram did not differentiate patients who did or did not develop AF. Patients who developed AF had a higher incidence of postoperative pneumonia (14 vs. 4%; P = 0.001), acute respiratory failure (8 vs. 1.6%; P = 0.01), greater hospital stay (17 ± 17 vs. 10 ± 9 days; P = 0.001) and 30-day mortality (11 vs. 3%; P = 0.001) when compared with those who did not develop AF, respectively. Conclusions: Advanced age and preoperative heart rate identify patients at high risk for development of AF after thoracic surgery. Postoperative AF occurs more frequently in patients with greater postoperative morbidity and length of hospitalization.